(untitled) (Journal of Surgical Sciences, 2026)
Breast cancer is the most common female cancer. Whereas Soft tissue sarcoma is a very rare cancer. Association of these two is extremely unusual entity. In the span of two years, from January 2016 to December 2017, we have encountered 4 unusual cases in Surgical Oncology Division, Department of Surgery, BSM Medical University. All of them presented with breast lumps with another lesion in limb or trunk of variable duration. Both the concurrent diseases were primary in nature. The age range of the patients was between 33 to 43 years. All the breast lesions were invasive ductal carcinoma. 3 out of 4 were triple negative breast cancer. 3 of the sarcomas were malignant fibrous histocytoma. All four of them underwent Mastectomy and wide excision of sarcoma in the single setting. They subsequently received adjuvant therapy. And all the patients are under regular follow-up. Journal of Surgical Sciences 2023;27(1): 18-22